Studi Pembuatan Siomai Dengan Penambahan Tepung Komposit Daun Kelor dan Hati Ayam - Adinda Silviana, Made Maya; Agustini, Ni Putu; Nanak Antarini, A.A. (Poltekkes Kemenkes Denpasar dan DPD PERSAGI Bali, 2024)
Siomai is a minced meat product wrapped in a thin skin made from wheat flour and cooked through a steaming process. In this study there was the addition of composite flour of moringa leaves and chicken liver. This study aims to determine the effect of the addition of moringa leaves and chicken liver composite flour on organoleptic quality, iron (Fe) content and antioxidant capacity in dumplings.This type of research is experimental with a randomized block design (RBD). The treatment given was 5 types of treatment with 3 repetitions. Data analysis used aims to determine the effect of treatment on organoleptic quality, levels of iron (Fe) and antioxidant capacity using analysis of variance (ANOVA). The results showed that there was an influence on organoleptic quality including aroma quality, taste quality, texture quality, overall acceptability, iron (Fe) content, and antioxidant capacity in dumplings. The addition of moringa leaf and chicken liver composite flour as much as 16% per weight of ground chicken meat resulted in the most widely accepted quality with characteristics of a non-pleasant aroma, savory taste, chewy texture, overall acceptance of likes, iron (Fe) content of 2.23 mg/ 100 g and antioxidant capacity of 0.0107%.Keywords : Dumplings, Composite Flour, Moringa Leaves, Chicken Liver, Iron, Antioxidant Capacity